GENETIC AND NON-GENETIC PARAMETERS FOR MILK PRODUCTION TRAITS OF DAMASCUS GOAT IN JORDAN - Khaleel I. Jawasreh,; Jalal E. Alkass, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study examined the effects of genetic and some non-genetic factors on total milk yield (TMY), test-day milk yield (TDM), pre-weaning (PRMY), and post-weaning milk yield (POMY) using a total of 1167 lactation records of (Damascus) does over the years of 1998 to 2001 at Al-Walla Agricultural Research Station, Ministry of Agriculture. The General Linear Model (GLM) was employed to analyze the data. TMY, TDM, PRMY, and POMY had respective overall averages of 280.3 kg, 1.45 kg, 135.7 kg, and 144.5 kg. Age, doe weight, birth type, and year of kidding all significantly influenced the variables under study.  Heritability estimates were 0.22, 0.17, 0.17 and 0.26 for TMY, TDM, PRMY and POMY, respectively. The corresponding estimates of repeatabilities were 0.44, 0.50, 0.32 and 0.33. Genetic correlation between studied traits ranged between 0.52 and 0.91.